2016
DOI: 10.3109/0284186x.2016.1161825
|View full text |Cite
|
Sign up to set email alerts
|

Experience with S-1 in older Caucasian patients with metastatic colorectal cancer (mCRC): Findings from an observational chart review

Abstract: Background: An aging population will increase the number of older patients with metastatic colorectal cancer (mCRC). However, there is limited knowledge about treatment in older patients as they are under-represented in clinical trials. The oral fluoropyrimidine S-1 is associated with a lower rate of adverse events than capecitabine and may therefore be a suitable drug for elderly. However, data on the use of S-1 in Caucasian mCRC patients are lacking/scarce. Material and methods: In the present study we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Non-hematological toxicities were very infrequent at the RD levels (3A and 2B). The RD of S-1 is in line with the S-1 dose commonly recommended for Caucasian patients [5,23,24], but lower than doses used in East Asian patients; which we believe is due to more effective bioactivation of tegafur to 5-FU caused by higher activity of CYP2A6 in Caucasian patients [25].…”
Section: Discussionsupporting
confidence: 69%
“…Non-hematological toxicities were very infrequent at the RD levels (3A and 2B). The RD of S-1 is in line with the S-1 dose commonly recommended for Caucasian patients [5,23,24], but lower than doses used in East Asian patients; which we believe is due to more effective bioactivation of tegafur to 5-FU caused by higher activity of CYP2A6 in Caucasian patients [25].…”
Section: Discussionsupporting
confidence: 69%
“…For the time being, S-1 in Europe has been only approved for gastric cancer therapy. With respect to CRC, the experience with S-1 is limited to promising retrospective data in older Caucasian patients 4. However, prospective randomised survival data from a Dutch cohort are expected to be published soon 10.…”
Section: Discussionmentioning
confidence: 99%
“…A completed randomised Nordic study (Nordic 9), including 156 eligible Caucasian patients, revealed higher response rates, longer PFS, less severe toxicity with dose reduced combination chemotherapy (oxaliplatin and S1 compared with full dose monotherapy (S1) as 1st-line treatment in elderly (older than 70 years) patients not candidates for full dose combination chemotherapy [31]. S1 was prior to the Nordic 9 study favourably tested in a phase II study [32]. Further, S1 did in a Dutch randomised phase II study in Caucasian patients show similar activity to capecitabine, but with a significantly lower incidence of hand-foot syndrome [33].…”
Section: Importance Of Dose Intensitymentioning
confidence: 99%